Age of Transition Readiness of Adolescents and Young Adults With Chronic Diseases in Oman: Need an Urgent Revisit. Issue 4 (5th January 2022) - Abdwani, Reem; al Saadoon, Muna; Jaju, Sanjay; Elshinawy, Mohamed; Almaimani, Asmaa; Wali, Yasser; Khater, Doaa
Abstract : Background: The Ministry of Health in Oman and some of Gulf regions set the cut-off age of "transfer" from child health care to adult health care at 13 years of age. Within the existing health system in this part of the world, there is paucity of evidence on the appropriate age for health care "transfer" of adolescents and young adults to adult health care. Similarly, there is lack of a structured health care "transition" program. The objective of the study is to indirectly determine the appropriateness of present cut-off age of transfer by studying readiness for transition among Omani patients suffering from chronic hematological conditions. Methods: One hundred fifty adolescents and young adults with chronic hematological conditions were recruited from pediatric and adults clinics at Sultan Qaboos University Hospital. Participants were interviewed by a trained research assistant using the Arabic version of UNC TRxANSITION Scale to assess self-management skills and health related knowledge for transition. The score range is 0 to 10; the transition readiness of the patients is assessed as low (0 to 4), moderate (4 to 6), and high (6 to 10) respectively. The continuous variables were analyzed by parametric or nonparametric methods as appropriate. χ 2 analysis was done to determine association of age groups within each sexes. Results: The study recruited 150 subjects (52.7% males) with 50 patients in each of the 3 age groups of 10 to 13 years (lower), 14 to 17 years (middle), and 18 to 21years (higher). The mean UNC TRxANSITION Scale scores of 5.14 (SD=1.27) in males in the total sample were significantly lower as compared with that of 5.67 (SD=1.50) in females ( P =0.022). There is a steady increase in the overall median score with increase in age group, with median score of 4.42 in the lower, 5.26 in the middle and 6.81 in the higher age group ( P <0.001). In section wise analysis, except for Adherence and Nutrition sections of the scale, all sections have statistically significant difference in the median scores across various age categories with lowest scores in the 10 to 13 age group and highest scores in the 18 to 21 years group. In the section related to reproduction, females had significantly higher mean ranks (31.52) and compared with 17.19 in males ( P =0.001). The overall median transition score when analyzed separately for males and females across age groups showed that in the higher age group, 67% of males ( P =0.008) and 90% females ( P <0.001) have high transition scores compared with the other 2 groups. Conclusions: Higher age was a significant predictor for transition readiness with median score being "moderate" in the lower and middle age groups, while the higher age groups scoring "high" on transition readiness. However, in the higher age group, the females (90%) showed better transition readiness than males (67%). The current age of transfer of 13 years is just at "moderate" levels. We recommend the need for establishing transition preparation program in Oman; increasing health transfer age in Oman to a cut-off age of 18 years and taking sex differences into consideration when providing interventions.